77.6k views
4 votes
3x+10y=13
4(-2y+x)-9x=13

User Lockdoc
by
5.1k points

1 Answer

6 votes

Answer:


x=-9


y=4

Explanation:


3x+10y=13 ← Equation 1


4(-2y+x)-9x=13\\

By simplifying the above equation we get,


-8y+=4x-9x=13 (Simplifying the brackets)


-8y-5x=13 (By subtracting
-9x from
+4x) ← Equation 2

Multiply Equation 1 by 5 and Equation 2 by 3 and add them together.

Equation 1 multiplied by 5 will give,


15x+50y=65

Equation 2 multiplied by 3 will give,


-24y-15x=39

Add those together,


15x+50y-24y-15x=65+39


26y=104 (After simplifying
x values)

Therefor
y=4

By substituting
y=4 to Equation 1 we get,


3x+10*4=13
3x+40=13\\3x=-27\\x=-9

Therefor we can say,


x=-9


y=4

User Miquelvir
by
6.1k points